1996
DOI: 10.1021/bi9608673
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Structural and Functional Characterization of FhuA, a Transporter of theEscherichia coliOuter Membrane

Abstract: The Escherichia coli outer membrane ferrichrome transporter FhuA was purified chromatographically in a neutral detergent (octyl glucoside or dodecyl maltoside). The amount of dodecyl maltoside bound to the protein (1.2 +/- 0.15 g/g of FhuA) and the Stokes radius of the FhuA-dodecyl maltoside complex (Rs = 4.2 nm) were determined using size exclusion chromatography. Sedimentation equilibrium and velocity experiments indicated that the FhuA preparation was monodisperse and that the protein was monomeric. The val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 46 publications
5
95
0
Order By: Relevance
“…Previous experiments [29] have shown that phage T5 ejects its DNA upon binding to purified FhuA, and DNA release can be measured using the fluorescent DNA intercalant YO-PRO- V f measurements, we calculated that the proportion of adsorbed phage decreased from 100 to 45 % when increasing the MccJ25 concentration from 0.1 to 3.2 µM (Figure 3). These values are in good agreement with the in vivo inhibition data (Figure 3).…”
Section: In Vitro Inhibition Of Dna Release Induced By Binding Of Phamentioning
confidence: 92%
See 2 more Smart Citations
“…Previous experiments [29] have shown that phage T5 ejects its DNA upon binding to purified FhuA, and DNA release can be measured using the fluorescent DNA intercalant YO-PRO- V f measurements, we calculated that the proportion of adsorbed phage decreased from 100 to 45 % when increasing the MccJ25 concentration from 0.1 to 3.2 µM (Figure 3). These values are in good agreement with the in vivo inhibition data (Figure 3).…”
Section: In Vitro Inhibition Of Dna Release Induced By Binding Of Phamentioning
confidence: 92%
“…MccJ25 and FhuA were purified as described previously [2,28] and quantified by amino acid composition analysis as in [21] , and peptide quantification was performed by amino acid composition analysis as described previously [29]. Peptide antibacterial activity was finally controlled according to the protocol described below.…”
Section: Peptide and Protein Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron micrograph shown in Fig. 3C indicated that the toroids formed were rather homogenous in size, with an outer diameter of 300 nm, and that a comparatively constant number of phages (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are involved in each structure.…”
Section: Resultsmentioning
confidence: 98%
“…Our strategy relies on the observation that the binding of bacteriophage T5 to its bacterial membrane receptor FhuA triggers the release of its genome, a double strand of 120,000 bp, linearly into the surrounding medium (15). Moreover, when FhuA is reconstituted in the membrane of a liposome, T5 phage bound to FhuA transfers its DNA directly into the liposome (16)(17).…”
mentioning
confidence: 99%